(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Sicilian Miocene silico—clastic sediments usually known as Terravecchia Formation have been studied with the aim of specifying the age and depositional environment of the formation by micropaleontologic observations. The study area was the Salemi—Castelvetrano basin, grossly spread between Trapani and Alcamo, at north, and Menfi and Mazara del Vallo, at South, in the southwestern part of Sicily. The study wag performed both on ditch and core samples of 6 named Agip wells and on surface samples.